Effectiveness of four different techniques in removing intracanal medicament from the root canals: An in vitrostudy - A C Bhuyan; Mukut Seal; Kartik Pendharkar (Wolters Kluwer Medknow Publications, 2015)
Aim: To evaluate the effectiveness of different techniques in removing calcium hydroxide (Ca(OH) 2 ) from the root canal. Materials and Methods: Twenty-four freshly extracted mandibular premolars were instrumented using ProTaper rotary instruments. The teeth were longitudinally split into two halves, cleaned of debris. The two halves were then reassembled and filled with Ca(OH) 2 and were divided into four groups. In Group I, the teeth were irrigated with 5 mL of 2.5% sodium hypochlorite (NaOCl) and 5 mL of 17% of ethylenediaminetetraacetic acid. In Group II, the teeth were irrigated with 5 mL of 2.5% NaOCl and a rotary ProTaper F3 instrument was used. In Group III, the teeth were irrigated with 5 mL of 2.5% NaOCl and agitated using an ultrasonic unit. In Group IV, the teeth were irrigated with 5 mL of 2.5% NaOCl and a CanalBrush was used to remove Ca(OH) 2 . The roots were disassembled, and photographs were taken. The amount of residual Ca(OH) 2 was calculated using an image analysis software as a percentage of the total canal surface area. The data were analyzed using one-way analysis of variance and post-hoc Tukey test. Results: CanalBrush and ultrasonic techniques showed significantly less residual Ca(OH) 2 than irrigants and rotary techniques. There was no significant difference between the rotary and irrigant techniques. Conclusion: None of the techniques used were completely able to remove Ca(OH) 2 from the root canals. But the CanalBrush and ultrasonic techniques were significantly better than the rotary instrument and irrigant groups.